Your Approach Should be Optimum

Algebra Level 4

If f ( x ) = ( x + 1 ) 2 ÷ ( x 2 + 3 ) f(x) ={(x+1)}^{ 2 }\div( x ^{ 2 }+3) and maximum value of f ( x ) = a / b f(x)=a/b where a and b are co-prime positive integers, what is a + b a+b ?

This is Part of set Click here
This is my first question on Brilliant.


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Deepanshu Gupta
Aug 5, 2014

N O T E : w e c a n w r i t e x + 1 = ( x + 3 1 3 ) { N o w u s e C a u c h y s c h z . i n e q u a l i t y } { x + 3 1 3 } 2 { x 2 + ( 3 ) 2 } × { 1 2 + ( 1 3 ) 2 } f ( x ) m a x = 4 3 a = 4 , b = 3 a + b = 7 NOTE:\quad we\quad can\quad write\longrightarrow \quad x+1=\quad (x+\sqrt { 3 } \sqrt { \frac { 1 }{ 3 } } )\\ \{ Now\quad use\quad Cauchy\quad schz.\quad inequality\} \\ \\ \Longrightarrow { \{ x+\sqrt { 3 } \sqrt { \frac { 1 }{ 3 } } \} }^{ 2 }\quad \le \quad { \{ x }^{ 2 }+{ (\sqrt { 3 } })^{ 2 }\} \times \{ { 1 }^{ 2 }+{ (\sqrt { \frac { 1 }{ 3 } } })^{ 2 }\} \\ \\ \Longrightarrow { f\left( x \right) }_{ max }=\frac { 4 }{ 3 } \\ \Longrightarrow a=4\quad ,\quad b=3\\ \Longrightarrow a+b=7\quad .

I Think This is best use of Cauchy inequality.

FYI - To type equations in Latex, you just need to add around your math code. I've edited your question so that you can refer to it.

Calvin Lin Staff - 6 years, 10 months ago
Mvs Saketh
Sep 22, 2014

( x + 1 ) 2 ( x 2 + 3 ) = 1 + 2 x 1 x 2 + 3 N o w m a x i m a o f 2 x 1 x 2 + 3 o c c u r s w h e n i t s d e r i v a t i v e i s 0 w h i c h o c c u r s w h e n 2 x ( x 1 ) = x 2 + 3 o r a t x = 1 a n d a t x = 3 c l e a r l y m a x i m a o c c u r s a t x = 3 , h e n c e m a x i m u m v a l u e i s 4 3 o r a + b = 7 \frac { \left( { x }+1 \right) ^{ 2 } }{ ({ x }^{ 2 }+3) } \quad =\quad 1\quad +\quad 2\frac { x-1 }{ { x }^{ 2 }+3 } \\ \\ Now\quad maxima\quad of\quad 2\frac { x-1 }{ { x }^{ 2 }+3 } \\ \\ occurs\quad when\quad its\quad derivative\quad is\quad 0\\ \\ which\quad occurs\quad when\quad 2x(x-1)\quad =\quad { x }^{ 2 }+3\\ or\quad at\quad x\quad =\quad -1\quad and\quad at\quad x\quad =3\\ \\ clearly\quad maxima\quad occurs\quad at\quad x\quad =3,\quad \\ hence\quad maximum\quad value\quad is\quad \\ \\ \frac { 4 }{ 3 } \\ \\ or\quad a+b\quad =\quad 7 .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...